Elevated metabolic rate and skeletal muscle oxidative metabolism contribute to the reduced susceptibility of NF‐κB p50 null mice to obesity - Bhatt, Bankim A. (Physiol Rep, 2018)
Mice with a deletion of the p50 subunit of the proinflammatory nuclear factor kappa B pathway (NF‐κB p50) have reduced weight compared to wild‐type control mice. However, the physiological underpinning of this phenotype remains unknown. This study addressed this issue. Compared to littermate controls, lean male p50 null mice (p50(−/−)) had an increased metabolic rate (~20%) that was associated with increased skeletal muscle (SkM, ~35%), but not liver, oxidative metabolism. These metabolic alterations were accompanied by decreases in adiposity, and tissue and plasma triglyceride levels (all ~30%). Notably, there was a marked decrease in skeletal muscle, but not liver, DGAT2 gene expression (~70%), but a surprising reduction in muscle PPAR α and CPT1 (both ~20%) gene expression. Exposure to a high‐fat diet accentuated the diminished adiposity of p50(−/−) mice despite elevated caloric intake, whereas plasma triglycerides and free fatty acids (both ~30%), and liver (~40%) and SkM (~50%) triglyceride accumulation were again reduced compared to WT. Although SkM cytokine expression (IL‐6 and TNF α, each ~100%) were increased in p50(−/−) mice, neither cytokine acutely increased SkM oxidative metabolism. We conclude that the reduced susceptibility to diet‐induced obesity and dyslipidemia in p50(−/−) mice results from an increase in metabolic rate, which is associated with elevated skeletal muscle oxidative metabolism and decreased DGAT2 expression.